Students Perceived Satisfaction With Online Learning - Murtiningsih, Retno Sari (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
Abstract This research is concerning how perceived challenges of e-learning, perceived learner motivation, interaction, and self-efficacy impact students perceived satisfaction. This study uses primary data collected by distributing questionnaires online (Google questionnaires). The population for this research is the students of Economics and Business, at Trisakti University. This research used purposive sampling technique with samples of 112 respondents. The dependent variable in this study is students' perceived satisfaction, while the independent variables are perceived challenges of e-learning, perceived learner motivation, interaction, and self-efficacy. This study used SEM-PLS. The results show that perceived learner motivation and self-efficacy positively influence students' perceived satisfaction while perceived challenges of e-learning and interaction do not affect students' perceived satisfaction.